Strategizing for project success in multifaceted public-sector stakeholder environments - Nalweyiso, Grace; Nangoli, Sudi; Muwanga, Robert; Byomire, Gorret; Musasizi, Yunia; Simiyu, Silvia W. (ournal of Economic, 2015)
Projects have various stakeholders whose expectations are diverse in nature and therefore the environment in which they operate is an issue of concern. This is achieved by knowing who these stakeholders are, understanding their interests or perceptions regarding the project and determining their level of influence towards the project in terms of power and above all the environments in which they operate. This study sought to examine the extent to which project stakeholder environments influenced project success of Universal Primary Education project in Uganda. It notes that the Universal Primary Education project in Uganda is categorized by poor quality performance and thus calls on strategies aimed at improving project success. Quantitative research methods were used. Questionnaires were used as the preferred data collection tool. Frequencies, means, correlations and regression data analysis techniques were used to draw inferences from collected and cleaned data. Data were collected from a sample of 181 Universal Primary Education schools operating in Central Uganda. Findings revealed that there is a positive significant relationship between the nature of stakeholder environments and perceived project success (r = .367, p < .01). Results also reveal that stakeholder environments predicted perceived project success (Beta = .453). The regression model was valid (sig. <.01). This means that the more supportive the Stakeholder environments are, the more successful Universal Primary Education project will be perceived to be by stakeholders. Thus, in order to ensure that Universal Primary Education is successfully implemented, there is need to provide better environment for various stakeholders. This could be in terms of improved working conditions of teachers, provision of teaching materials, and good classrooms among others.
Keywords: Perceived project success; Strategy; Stakeholder environments; Universal Primary Education